Absence of 2.5 power law for fractal packing in metallic glasses. (29th May 2018) - Feng, Jianrui; Chen, Pengwan; Li, Mo
Abstract: Atomic packing is still a mystery for topologically disordered amorphous solids owing primarily to the absence of Bragg diffraction in this class of materials. Among many hypotheses, fractal packing is suggested based on a scaling relation with '2.5 power law' found in multicomponent metallic glasses. Here we examine the atomic packing critically in a pure Tantalum metallic glass under hydrostatic pressure. Without complications of chemical compositions as in the multicomponent systems, the genuine amorphous structure along in the single component metallic glass exhibits a cubic scaling exponent that indicates absence of the 2.5 power law. However, fractal-like short- and medium-range icosahedral cluster packing is observed; but these substructures do not contribute to the fractal dimension through the power law scaling.